2021
DOI: 10.3390/ijms23010356
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Efficacy of Aspalathin and Other Related Phytochemicals in Type 2 Diabetes—A Review

Abstract: In the pursuit of bioactive phytochemicals as a therapeutic strategy to manage metabolic risk factors for type 2 diabetes (T2D), aspalathin, C-glucosyl dihydrochalcone from rooibos (Aspalathus linearis), has received much attention, along with its C-glucosyl flavone derivatives and phlorizin, the apple O-glucosyl dihydrochalcone well-known for its antidiabetic properties. We provided context for dietary exposure by highlighting dietary sources, compound stability during processing, bioavailability and microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 148 publications
(196 reference statements)
0
11
0
Order By: Relevance
“…Rooibos is prepared from either leaves or stems, and consumption of it has been increasing because of its health benefits and caffeine-free composition, compared to other teas [ 103 ]. In addition, this plant has a unique flavonoid profile including dihydrochalcone aspalathin in both fermented and non-fermented rooibos, which has been demonstrated to help with type-2 diabetes slowdown [ 104 ]. Non-exclusive polyphenols, such as orientin, isoorientin, isoquercitrin, rutin, and quercetin, have also been described in rooibos [ 105 ].…”
Section: Hibiscus Rooibos Yerba Mate As Sources Of Natural Bioactive ...mentioning
confidence: 99%
“…Rooibos is prepared from either leaves or stems, and consumption of it has been increasing because of its health benefits and caffeine-free composition, compared to other teas [ 103 ]. In addition, this plant has a unique flavonoid profile including dihydrochalcone aspalathin in both fermented and non-fermented rooibos, which has been demonstrated to help with type-2 diabetes slowdown [ 104 ]. Non-exclusive polyphenols, such as orientin, isoorientin, isoquercitrin, rutin, and quercetin, have also been described in rooibos [ 105 ].…”
Section: Hibiscus Rooibos Yerba Mate As Sources Of Natural Bioactive ...mentioning
confidence: 99%
“…An important aspect that should be considered is the fact that aspalathin, despite its high antiglycation as well as trapping properties, has an extremely low level of bioavailability—at less than 1% [ 75 ]. However, aspalathin as a C-glycoside is metabolized with the involvement of bacterial enzymes in the large intestine, where low-molecular metabolites, such as phloroglucinol, have the chance to be absorbed into the circulation and can have a systemic antiglycation and trapping effect [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aspalathin is the specific flavonoid to Rooibos, and it is abundantly present in Aspalathus linearis , which explains the huge amount of interest in the potential health benefits of this flavonoid. The other four main flavonoids (nothofagin, orientin, isoorientin and vitexin) in Rooibos extract are not specific and may occur in other medicinal plants such as Leandra dasytricha [ 25 ]. The Rooibos extract used in our study contains 80 g·kg −1 aspalathin, which is in the range of the natural products containing Rooibos (8–12%) [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rooibos tea has been consumed since the late 1700s, but its potent antioxidant activity and health-giving properties have only been reported in the past two decades, increasing its popularity [ 24 ]. Thus, Rooibos has attracted the attention of several research groups, and multiple in vivo and in vitro studies have demonstrated its significant effect on insulin resistance, diabetes, cardiovascular complications (mainly as an anti-hypertensive, through inhibition of angiotensin-converting enzyme), inflammation, viral infections, ovarian function, and others [ 24 , 25 ]. The anti-obesity potential of Rooibos extract was first reported in 2011 [ 26 ]; then, a research group demonstrated its effect on murine preadipocyte cells, but no more data were found on its impact on human adipocytes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%